Tropical Plant Species and Technological Interventions for Improvement - Sarwar Khan, Muhammad (IntechOpen, 2023)
This book provides a precise and meticulous overview of the production technologies involved in the cultivation of tropical plants. Technological advances have transformed the cultivation of fruit and ornamental plants from agronomic to value-added plants. The book highlights the essentials for developing tropical plants with increased nutritive, nutraceutical, and aesthetic value.